The Influence of Gamolan Musical Instrument Media on Children's Musical Abilities in Group B RA Perwanida 2 Palembang - Mustiana, Fadia; Oktamarina, Lidia; Hamzah, Amir; Marlina, Leny; Sartka, Indah Dwi (Al-Mudarris, 2025)
This study was motivated by evidence that Group B children at RA Perwanida 2 Palembang had low musical ability, shown by undirected instrument play and weak scale recognition, likely due to limited music-learning media. Because music in early childhood provides sensory–emotional stimulation through play consistent with Developmentally Appropriate Practice (DAP), this research examined whether the traditional gamolan instrument could enhance musical ability while supporting Islamic educational aims such as cultivating aesthetic sensitivity (jamal), rhythmic discipline, gratitude, and awareness of God’s orderly creation. A quantitative pre-experimental method with a one-group pretest–posttest design was used. From a population of 137 children (classes B1–B7), 17 children in class B1 were selected purposively. Data were collected through observation, documentation, and musical ability tests, then analyzed with validity, reliability, normality, homogeneity, and t-test procedures. Results indicated clear improvement after gamolan-based learning: the mean score rose from 21.41 (pretest) to 52.00 (posttest), with tcount 11.600 exceeding ttable 2.131 at α = 0.05, leading to rejection of H0. Thus, gamolan significantly improves children’s musical ability, offering joyful, play-based learning that sharpens auditory sensitivity, emotional control, and rhythmic discipline, strengthens local cultural identity, and supports positive character growth in early grades.